2016
DOI: 10.1039/c5cp07298k
|View full text |Cite
|
Sign up to set email alerts
|

Structural determination of niobium-doped silicon clusters by far-infrared spectroscopy and theory

Abstract: In this work, the structures of cationic Si n Nb + (n = 4-12) clusters are determined using the combination of infrared multiple photon dissociation (IR-MPD) and density functional theory (DFT) calculations. The experimental IR-MPD spectra of the argon complexes of Si n Nb + are assigned by comparison to the calculated IR spectra of low-energy structures of Si n Nb + that are identified using the stochastic 'random kick' algorithm in conjunction with the BP86 GGA functional. It is found that the Nb dopant tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 79 publications
(159 reference statements)
2
27
0
Order By: Relevance
“…According to our calculations, one can find that the transitions between 3D to 2D clusters tend to be increased energetically, and the 3D trigonal bipyramid structure (in low‐spin states) with an apical metal atom in C 3v symmetry is the putative GM for all the studied systems. Of which, the 3D Si 4 Nb + structure has been previously assigned using the infrared multiple photon dissociation spectroscopy in combination with DFT computations . One can see that the sole silicon or germanium atom energetically favors to occupy the equatorial (Figure a, isomer B, C s symmetry) or another apical (Figure a, isomer A, C 3v symmetry) position for metal‐doped SiGe 3 and Si 3 Ge bases, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…According to our calculations, one can find that the transitions between 3D to 2D clusters tend to be increased energetically, and the 3D trigonal bipyramid structure (in low‐spin states) with an apical metal atom in C 3v symmetry is the putative GM for all the studied systems. Of which, the 3D Si 4 Nb + structure has been previously assigned using the infrared multiple photon dissociation spectroscopy in combination with DFT computations . One can see that the sole silicon or germanium atom energetically favors to occupy the equatorial (Figure a, isomer B, C s symmetry) or another apical (Figure a, isomer A, C 3v symmetry) position for metal‐doped SiGe 3 and Si 3 Ge bases, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Up to date, although previously significant studies involving structural and electronic properties have been widely carried out for the metal‐doped semiconductor clusters, for example, neutral Si n TM (TM = Fe, Ru, Os, Hf, V, Mn, Co, Zr) and cationic Si n TM + (TM = V, Mn, Cu, Ag, Au, Nb), there are few works that are available for probing the chemical nature of the bonding between TM and the semiconductor cluster, in which the bonding features are largely responsible for understanding the high stability of doped clusters. With this motivation, we have performed a systematic study for the Si x Ge y M + ( x + y = 4; M = Nb, Ta) species with 20 valence electrons, which can serve as typical model systems to study the spherical aromaticity and chemical bonding of closed‐shell species containing metal atom, and explore the doping effect of the TM atoms on the mixed Si‐Ge tetramers.…”
Section: Introductionmentioning
confidence: 99%
“…At the hybrid B3LYP level, the E g value of the complex is predicted to be 2.90 eV, which is calculated from the HOMO (−6.02 eV) and the LUMO (−3.12 eV). A large E g value is strongly related with high‐kinetic stability . This is because that the compounds with the large gaps are energetically unfavorable to add electrons to a high‐lying LUMO or to extract electrons from a low‐lying HOMO, and to form the activated compounds of any potential reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Geometry optimizations of the RhCD complexes were performed by DFT with the hybrid B3LYP functional in conjunction with Karlsruhe split‐valence def‐SVP basis set augmented with polarization functions for all the atoms, as implemented in the Gaussian 09 programs . The method provides a better energy prediction for evaluating the structural stability of complexes . In the computation, the singlet and triplet spin states (spin multiplicities 2 S + 1 = 1, 3) were considered for initial structure.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In this context, the structures of cationic SinNb+, SinV+, SinCo+, SinMn+ etc. clusters have also been determined using the above mentioned method [13][14][15]. Though it is suggested that for large doped silicon clusters, multiple isomers can coexist and contribute to measured infrared spectra, making the judgement on ground-state cluster structures no longer straightforward.…”
Section: Introductionmentioning
confidence: 99%